Preparation and characterization of composite phase change materials based on paraffin and carbon foams derived from starch. (6th January 2021) - Shi, Tengteng; Zhang, Xiaoguang; Qiao, Jiaxin; Wu, Xiaowen; Chen, Guo; Leng, Guoqin; Lin, Fankai; Min, Xin; Huang, Zhaohui
Abstract: In this paper, a composite phase change material based on paraffin and carbon foam derived from starch was prepared. The paraffin was encapsulated in the carbon foam, which was prepared by using a foaming and steaming method at different carbonization temperatures. Carbon foams comprised amorphous carbon and were impregnated with paraffin to obtain the paraffin/carbon foam composites (PCCs). When carbonized at 1100 °C, the loading percentage of the carbon foam enabled to reach maximum 72.79%. Paraffin encapsulation did not result in any new structure or chemical bonds involved or change in the geometry. The latent heats of the sample were 174.3 J/g at the melting temperature (47.9 °C), and 151.4 J/g at the freezing temperature (52.8 °C). Thermal conductivity of PCCs reached up to 1.93 times than that of paraffin. The composite phase change material fabrication was cost–effective, environment friendly, chemically stable, and suitable for energy–efficient building applications. Graphical abstract: Image 1 Highlights: The carbon foam with hierarchical pores was prepared by traditional thermal fermentation and steaming method. The paraffin was encapsulated in the carbon foam without any new structure or chemical bonds involved in the geometry. Thermal conductivity of the composite phase change materials reached up to 1.93 times that of paraffin. The composite PCM fabrication was environment friendly, and suitable for energy–efficient building applications.